Explanatory modelling of factors influencing adoption of smartphone shopping application - Bernardo, Ezekiel (Animo Repository, 2019)
Smartphone shopping applications are in the spotlight in the current Philippine setting of m-commerce adoption. This momentum flourished over the last decade as its capabilities, accessibility, and functionality became greatly detrimental to the present way of living. However, even with the shift, very few studies have been conducted that aims to explain the rise in the adoption of m-commerce specifically smartphone shopping applications. Qualitative claims are abundant but no quantified measures have been established which leaves a gap in the understanding of the growth. Responding to that, this study proposes a model that aims to explore the factors influencing the adoption of smartphone shopping applications that can be used by the industry. Specifically, factors under the UTAUT2 model with trust construct in terms of security, privacy, and information quality under the condition of behavioral intention and use behavior. Data from Filipino consumers were gathered using online questionnaires and were analyzed using structural equation modeling. The result shows that the proposed model captured 0.643 and 0.712 explaining power for intention and behavior respectively while 0.557 for trust construct which confirms the robustness of the novelty model. The study reveals that perceived trust in the system and having references for the use of commerce are the most important factor for intention and behavior. Moreover, the behavior is also catalyzed by social influence, hedonic motivation and perceived productiveness when using the application. More so, the effort needed to use the application and monetary cost needed to acquire such applications are not relevant to the growth. © 2019 KIIE.